Embedded For You: Vol.4 Issue.5 Sept-Oct '2010 (electronic chip additional) (Academy of Embedded Technology Delhi, 2010)
2009 Vol.4 Issue No.1 (Jan-Feb) 23-3-2010 Issue No.2 (Mar-Apr) 08/06/2009 Issue No.3 (May-Jun) 22/07/2009 Issue No.4 (July-Aug) 22/07/2009
Keywords: Electronics/ Embedded Technology